2015
DOI: 10.1007/s00432-015-1967-5
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of discoidin domain receptor 2 decreases tumor growth of hepatocellular carcinoma

Abstract: The inhibition of DDR2 by RNA interference suppressed in vivo and in vitro growth of human HCC cells. Our results may support that the use of DDR2 as a novel target of HCC treatment through control of tumor apoptosis, migration, and invasion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 24 publications
2
17
0
Order By: Relevance
“…Taking into account the IHC data, where no further increase between primary tumors and lymph node metastases was evident, one could suggest that DDR2 mainly supports the metastatic spread of the primary tumor but plays only a minor role after formation of metastases. The importance of DDR2 for metastatic spread has already been proven in several tumor entities such as melanoma, liver‐ and breast cancer . A crucial step in the formation of metastases is adhesion when evading lymphatic‐ and blood vessels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking into account the IHC data, where no further increase between primary tumors and lymph node metastases was evident, one could suggest that DDR2 mainly supports the metastatic spread of the primary tumor but plays only a minor role after formation of metastases. The importance of DDR2 for metastatic spread has already been proven in several tumor entities such as melanoma, liver‐ and breast cancer . A crucial step in the formation of metastases is adhesion when evading lymphatic‐ and blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of DDR2 for metastatic spread has already been proven in several tumor entities such as melanoma, liver-and breast cancer. 18,21,44 A crucial step in the formation of metastases is adhesion when evading lymphatic-and blood vessels. Our data demonstrates that DDR2 increases adhesion on cell-culture coated plates but not on collagen I coated plates for both analyzed cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Hammerman and colleagues showed that a subset of DDR2 mutations, including L63V, I638F, and S768R, mediated an oncogenic effect (25). A recent study demonstrated that the inhibition of DDR2 suppressed the in vivo and in vitro growth of human hepatocellular carcinoma cell lines (26). In contrast, the activation of DDR2 by collagen has been shown to inhibit the proliferation of human melanoma and fibrosarcoma cell lines (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…High DDR2 expression is correlated with poor prognosis (122). DDR2 overexpression facilitates migration, invasion, and the EMT of HCC by activating ERK2 and stabilizing Snail1, whereas DDR2 silencing in HCC decreases the EMT, Snail1 half-life, and invasion but increases cell death (122, 123). …”
Section: Hepatocellular Carcinomamentioning
confidence: 99%